First section of the course performance as a critical aspect in skicross competition: 2010 olympic games and world cup analysis - Argüelles, J.; De La Fuente, B.; Tarnas, J.; Dominguez-Castells, R. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
Skicross (SX) is a winter sports discipline that consists of racing across an uneven track with jumps, banked turns and other obstacles. The 56 heats of the 2010 most important competitions were studied: Vancouver Olympic Winter Games (OWG) and Sierra Nevada World Cup Final (WCF). In both races we analyzed the skiers rank at each heat's first turn as well as their final rank at the finish. A great percentage of riders that were ahead at the first turn of the race, classified in the top two positions and reached the next round: OWG, (87,5%) m and w; WCF, m (81,25%) and w (87,5% ). These results suggest that a fast first section of the course can contribute to race success. Specific start training becomes necessary to compete at SX high level.